Study Protocol: national research partnership to improve primary health care performance and outcomes for Indigenous peoples - Bailie, R.; Si, D.; Shannon, C.; Semmens, James; Rowley, K.; Scrimgeour, D.; Nagel, T.; Anderson, I.; Connors, C.; Weeramanthri, T.; Thompson, Sandra; McDermott, R.; et al. (BioMed Central, 2010)
Strengthening primary health care is critical to reducing health inequity between Indigenous and non-Indigenous Australians. The Audit and Best practice for Chronic Disease Extension (ABCDE) project has facilitated the implementation of modern Continuous Quality Improvement (CQI) approaches in Indigenous community health care centres across Australia. The project demonstrated improvements in health centre systems, delivery of primary care services and in patient intermediate outcomes. It has also highlighted substantial variation in quality of care. Through a partnership between academic researchers, service providers and policy makers, we are now implementing a study which aims to 1) explore the factors associated with variation in clinical performance; 2) examine specific strategies that have been effective in improving primary care clinical performance; and 3) work with health service staff, management and policy makers to enhance the effective implementation of successful strategies.